A Novel Application of Photovoice in a Statewide Home Visiting Evaluation. (September 2021) - Agu, Ngozichukwuka; Rojas, Dogeli; Foti, Tara; Birriel, Pamela C.; Delva, Jennifer; Bello, Temitope; Sharon, Vanessa; Kaushik, Shruti; Marshall, Jennifer
Photovoice is an empowering, qualitative, community-based participatory research method that engages participants to take photographs and reflect on their meanings. We employed a novel application of a Photovoice-inspired methodology to evaluate perinatal home visiting services. This article describes the feasibility and utility of remote implementation of a Photovoice-inspired project in one state's federally funded Maternal, Infant, and Early Childhood Home Visiting Initiative. The initial project aimed to identify aspects of parenting roles/identities, goals, and home visitor–client relationship that can be leveraged to improve program engagement and retention. Training materials were sent to home visitors who acted as liaisons with parents. Reflective interviews about this photo-elicitation method conducted with parents, home visitors, and the evaluators following the project revealed that informational materials were beneficial to understanding the process. Home visitors were noted as gatekeepers and key motivators. Trainings, flexibility, timely communication, and logistics should be considered when remotely implementing Photovoice.